The Pioneering Stage in Input-Output Economics: The Soviet National Economic Balance 1923-24, After Fifty Years - Spulber, Nicolas; Dadkhah, Kamran Moayed (The Review of Economics and Statistics, 1975)
Nicolas Spulber, Kamran Moayed Dadkhah, The Pioneering Stage in Input-Output Economics: The Soviet National Economic Balance 1923-24, After Fifty Years, The Review of Economics and Statistics, Vol. 57, No. 1 (Feb., 1975), pp. 27-34